2012
DOI: 10.1007/s10735-012-9442-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of apoptosis and proliferation of acinar cells in atrophy of rat parotid glands induced by liquid diet

Abstract: Parotid glands of experimental animals fed a liquid diet are reported to show atrophy (Hall and Schneyer 1964;Wilborn and Schneyer 1970;Hand and Ho 1981;Scott et al. 1990;Scott and Gunn 1991). To clarify whether apoptosis and proliferation of acinar cells participate in atrophy of rat parotid glands induced by liquid diet, rats were fed a liquid diet and compared to pellet-fed controls. Parotid glands were removed at 3, 7, 14 or 21 days, weighed, and examined using transmission electron microscopy (TEM), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…We demonstrated that a liquid diet did not induce atrophy in submandibular and sublingual glands, although parotid glands became atrophic under the same experimental conditions (Takahashi et al, 2012). This agreed with previous findings in submandibular (Ekstrom, 1973;Mansson et al, 1990;Kurahashi and Inomata, 1999) and sublingual glands (Ekstrom, 1973;Scott and Gunn, 1991) in studies using the same experimental conditions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We demonstrated that a liquid diet did not induce atrophy in submandibular and sublingual glands, although parotid glands became atrophic under the same experimental conditions (Takahashi et al, 2012). This agreed with previous findings in submandibular (Ekstrom, 1973;Mansson et al, 1990;Kurahashi and Inomata, 1999) and sublingual glands (Ekstrom, 1973;Scott and Gunn, 1991) in studies using the same experimental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggested that changes in tissues of animals fed a liquid diet were not caused by changes in general health, because body weight loss or a general deterioration in health was not observed (Hall and Schneyer, 1964;Johnson, 1982;Mansson et al, 1990;Scott et al, 1990;Kurahashi and Inomata, 1999;Takahashi et al, 2012). In the present study, the body weights of experimental rats increased constantly and were not significantly different from those of controls, confirming the findings of previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the physical and chemical properties of foods affect salivary glands morphology and histology [126][127][128][129]. Although the regulation of the secretory activity of salivary glands has been almost exclusively attributed to the autonomic nervous system [130], recent evidences suggest that during variations in appetite and food intake the glands are probably also regulated by gastric (gastrin) and intestinal (cholecystokinin and melatonin) hormones [131][132][133].…”
Section: Electrophoresis In Formalin-fixed and Paraffin-embedded Tissmentioning
confidence: 99%